2009
DOI: 10.1002/bdra.20573
|View full text |Cite
|
Sign up to set email alerts
|

Maternal thyroid disease, thyroid medication use, and selected birth defects in the National Birth Defects Prevention Study

Abstract: Our results are consistent with the positive associations between maternal thyroid disease or thyroid medication use and both hydrocephaly and hypospadias observed in some previous studies. New associations with left ventricular outflow tract obstruction heart defects and anorectal atresia may be chance findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 21 publications
1
36
1
2
Order By: Relevance
“…One rather small study did not find an association between ARM and maternal fever during pregnancy either (Stoll et al, ), whereas three other studies showed increased risks of ARM for mothers who had a fever during the first trimester of pregnancy (van Rooij et al, ; Wijers et al, ; Wijers et al, ), mainly in ARM with other congenital malformations (Wijers et al, ). Chronic thyroid disorders and two gastrointestinal disorders (severe chronic dyspepsia and primary peptic ulcer disease) seemed to be associated with ARM as well, especially with isolated ARM (Ács et al, ; Browne et al, ; Bánhidy et al, ). Strong associations were found between phenotypic subgroups of ARM and maternal epilepsy in a large European study (Wijers et al, ), but not in another small study (Stoll et al, ).…”
Section: Nongenetic Factorsmentioning
confidence: 99%
“…One rather small study did not find an association between ARM and maternal fever during pregnancy either (Stoll et al, ), whereas three other studies showed increased risks of ARM for mothers who had a fever during the first trimester of pregnancy (van Rooij et al, ; Wijers et al, ; Wijers et al, ), mainly in ARM with other congenital malformations (Wijers et al, ). Chronic thyroid disorders and two gastrointestinal disorders (severe chronic dyspepsia and primary peptic ulcer disease) seemed to be associated with ARM as well, especially with isolated ARM (Ács et al, ; Browne et al, ; Bánhidy et al, ). Strong associations were found between phenotypic subgroups of ARM and maternal epilepsy in a large European study (Wijers et al, ), but not in another small study (Stoll et al, ).…”
Section: Nongenetic Factorsmentioning
confidence: 99%
“…We found elevated ORs for these defects in the current analysis of births from 1997 to 2011, but all three estimates were smaller in magnitude than previously reported, and our hypospadias OR was not statistically significant in the current analysis. We found significant associations with five birth defects previously examined in the NBDPS, but not found to be significantly associated with thyroid hormone use: anencephaly, holoprosencephaly, small intestinal atresia, isolated cleft palate, and isolated longitudinal limb deficiency (Browne et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on crude ORs, anti‐thyroid medication use was significantly associated with aortic valve stenosis. The previous NBDPS analysis identified two elevated crude associations with anti‐thyroid medication: aortic valve stenosis and anorectal atresia (Browne et al, ). The previous and current NBDPS analyses included the same exposed aortic valve stenosis cases ( n = 3) and anorectal atresia cases ( n = 4); no additional exposed cases were identified from 2005 to 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge is therefore to design treatments that are effective and do not pose an additional, or different, risk to the conceptus as compared to the disease itself. For instance, as hyperthyroidism has been reported in 3% of pregnant women [27], a balanced therapy has been proposed with propylthiouracil (less damaging to the embryo but inducing long-term liver toxicity) in the first trimester, followed by the use of methimazole (which has a higher teratogenic potential but lower maternal toxicity) [21]. However, for chronic conditions, the primary prevention of CA and other adverse pregnancy outcomes has to integrate patient-oriented periconceptional actions with actions at the community level involving food, lifestyle and health care.…”
Section: Tablementioning
confidence: 99%